Infectiousness to sand flies of a cat naturally infected with Leishmania infantum at the moment of diagnosis and after three different courses of treatment - Mariana Dantas da Silva; Andrea Cristina Higa Nakaghi; Fredy Galvis-Ovallos; João Augusto Franco Leonel; Geovanna Vioti; Eunice Aparecida Bianchi Galati; Nayara Cristina de Oliveira Fazolato; Julia Pinho Martins; Trícia Maria Ferreira de Sousa Oliveira (Revista Brasileira de Parasitologia Veterinária)
Abstract In this study, an evaluation was made of three treatments against feline leishmaniosis (FeL) and their impacts on the transmission of Leishmania infantum to its vector, Lutzomyia longipalpis. A cat with clinical signs of FeL was examined and L. infantum diagnosed. Subsequently, the cat was subjected to xenodiagnosis and L. infantum detected in the vectors. The cat was then treated with three different drugs and the clinical improvement and parasite transmissibility to the vector were evaluated. Promastigotes were observed in 21/52 female sandflies (40.38%) in a xenodiagnosis prior to the treatments. Clinical signs persisted after the first treatment with marbofloxacin, and the cat remained positive in serological, molecular, and parasitological tests. Therefore, the cat was treated with miltefosine but remained sick and tested positive. A second xenodiagnosis was performed a month after treatment with miltefosine, and promastigotes were observed in 5/9 females (55.55%). Lastly, the cat was treated with allopurinol, which led to good clinical improvement, but it remained positive, and a final xenodiagnosis revealed Leishmania in 2/29 (6.89%) females. The results showed that only treatment with allopurinol produced a good clinical response, but none of the treatments succeeded in eliminating L. infantum infection or preventing transmission to the vector.